GYPSUM GROWTH IN THE PRESENCE OF GROWTH INHIBITORS: A SCANNING FORCE MICROSCOPY STUDY - Bosbach D.; Hochella M.F. (My University, 1996)
The growth inhibiting and habit modifying effect of phosphonic acid derivatives (HEDP, ENTMP) and carboxylates (tartrate, citrate) on gypsum was investigated by in-situ Scanning Force Microscopy (SFM). Kinetic and morphological effects of additives on advancing monolayer steps were imaged. Adsorbed HEDP and ENTMP molecules attach to step edges, which results in a change in step morphology. It is shown that inhibitor concentration and the reactivity of step edges strongly influence the change in step morphology. At low inhibitor concentrations linear steps become jagged, whereas high inhibitor concentrations lead to smoothly curved step edges. On the (010) surface [101] steps are more reactive compared to [001] steps. Therefore [101] steps show the most significant change in step morphology. In-situ experiments in the presence of citrate clearly show reduced growth rates although monolayer steps still appear crystallographically aligned. Ex-situ images of gypsum crystals exposed to tartaric acid reveal that an amorphous coating has been precipitated at high tartrate concentrations, whereas low tartrate concentrations result in jagged or curved steps. In-situ SFM experiments confirm the increased inhibition effect of phosphonic acid derivatives compared to carboxylates.